Metal forming with flexible tools for sheet metal and tubular products - Thiruvarudchelvan, Sinnathamby. (2008)
Using flexible tools a novel technique of friction-actuated blank holding has been developed for drawing cylindrical, conical and hemispherical cups. Flexible tools have also been used to develop a method of bulging metal tubes. Tooling for the above processes have been designed,fabricated and tested. Theoretical analyses were also developed to predict the process parameters in these processes. Experimental investigations were carried out and the advantages and limitations of the processes are established.